Criminogenic risks of irregular migration in conditions of armed conflict in Ukraine - Lytvynov, Oleksii M.; Orlov, Yurii V.; Yashchenko, Andrei M.; Yurtayeva, Kseniya V. (DIXI, 2021)
The purpose of the paper is to comprehend and examine dimensions of irregular migration, namely its criminogenic, victimological sources and its background influence on criminal processes in conditions of armed conflict in Ukraine. Results of the study allows us to draw a sound conclusion that irregular migration poses a number of criminogenic risks to Ukrainian national security as well as to the rights and freedoms of Ukrainian citizens, especially of those who remain or arrive to the occupied territories. The research ascertains that criminogenic potential of migration may be viewed from two related perspectives associated with the phenomenon of migrants’ criminality and migrants as potential or real victims of crime. The research outlines the factors providing a favourable environment for engaging irregular migrants into criminal activities. Basing on the recent amendments to the Criminal Code of Ukraine and current criminal statistic the research ascertains the links of ethnic minority criminality and mercenary activities with irregular migration in Ukraine. The research provides arguments that internally displaced persons can be viewed as a contemporary type of intra-state migration that poses additional criminogenic hazards in conditions of the armed conflict in Ukraine. Practical implications of the study lie in the recommendations for decreasing the risks of irregular migration, in conditions of armed conflict in Ukraine, defined a following: resolving the issue on the legal status of the armed conflict in Eastern regions of Ukraine, as well as recognising Lugansk Public Republic and Donetsk Public Republics terrorist’s organisations on the national level. Reinforcing suppression of all kinds of smuggling, international. The same way, with the occupied territories, providing legal and psychological support to the victims of human trafficking and to the internally displaced persons; intensification of aware-ness-raising campaign on the risks on migrant smuggling and human trafficking among Ukrainian citizens, including the population of the affected conflict regions; reinforcing the fight against organized crime, and paying a specific attention at counteracting ethnic minority criminality. Finally, enhancing organizational bases and legal support in the field of counteracting irregular migration.